The Responses of Mulch Closure on the Germination of Mindi (Melia azedarach Linn.) - Nurmawati Siregar (Jurnal Perbenihan Tanaman Hutan, 2017)
One of the factors that determine the successful of the development of mindi is the availability of seedling. The seedlings can be propagated generatively by using seeds, however there is a problem related to the hardness of the testa that make it difficult to germinate, so it needs environment condition treatments to get optimal germination, one of this is mulching. The use mulch possibly get the improvement of temperature, humidity, infiltration and evapotranspiration. The study is aimed to determine the effect of mulch and to find out the best mulch type on the germination of mindi (Melia azedarach Linn.) seed. Randomized completely design was employed that arranged factorially, consisted of (A) mulch types factor and mulch thicknesses factor (B). There were 5 (five) types of mulch treatment i.e rice straws, transparent plastics, dark plastics, zeolite and without mulch. The thicknesses of mulch consisted of one layer and two layers of mulch. Germination capacity, germination speed and growth simultaneously were observed. The results showed, mulching effect on germination mindi the best type of mulch is black or transparent plastic mulch while the thickness of the mulch does not affect the germination. Mindi seed capable of germination in the dark and light conditions on the conditions of temperature and humidity high temperatures.